Odpowiedzi

2010-03-14T13:04:51+01:00
A)-3x=2x-10
-3x-2x=-10
-5x=-10/(-5)
x=2
b)2x-2=7-x
2x+x=7+2
3x=9/3
x=3
c)10=4-2x
2x=4-10
2x=-6/2
x=-3
d)-(2x-1)=4
-2x+1=4
-2x=4-1
-2x=3/(-2)
x=-3/2
x=-1,5
e)2(x+1)=x
2x+2=x
2x-x=-2
x=-2
f)2t-(3t+1)=6
2t-3t-1=6
2t-3t=6+1
-1t=7/(-1)
t=-7
g)-(4+x)=2(3-x)
-4-x=6-2x
-x+2x=6+4
x=10
h)3(y+6)-y=2(y+9)
3y+18-y=2y+18
3y-y-2y=18-18
0=0
i)(x-7)-2(3x+5)=3
x-7-6x-10=3
x-6x=3+7+10
-5x=20/(-5)
x=-4
1 5 1
2010-03-14T13:06:49+01:00
A)-3x=2x-10 /-2x
-5x=-10 /÷(-5)
x=2
b)2x-2=7-x /+2
2x=9-x /+x
3x=9 /÷3
x=3
c)10=4-2x /-4
-2x=6 /÷(-2)
x=-3
d)-2x+1=4 /-1
-2x=3 /÷(-2)
x=-3/2=-1½
e)2x+2=x /-2x
2=-x
x=-2
f)2t-3t-1=6 /+1
-t=7
t=-7
g)-4-x=6-2x /+4
-x=10-2x /+2x
x=10
h)3y+18-y=2y+18 /-18
2y=2y
to równanie ma wiele rozwiązań. :)
i)x-7-6x-10=3 /+17
-5x=20
x=-4